Effect of Mosaic Allograft Osteochondral Transplantation Combined with Corrective Osteotomy in Treating Osteochondral Lesions of the Talus on Ankle and Knee Joint Function and Lower Limb Alignment. (15th July 2022) - Zhao, Zhenshuan; Li, Jun; Yu, Xiaoguang; Liu, Guobin; Zhao, Feng; Li, Ruiqi
Abstract : Objective . To explore the effect of mosaic allograft osteochondral transplantation combined with corrective osteotomy in treating osteochondral lesions of the talus (OLT) on ankle and knee joint function and lower limb alignment. Methods . One hundred and thirty-three OLT patients treated in our hospital between July 2015 and October 2019 were enrolled. Regarding the various surgical approaches, they were categorized into two groups, namely, A and B including 69 and 64 cases, respectively. The patients in group A were processed with mosaic allograft osteochondral transplantation combined with corrective osteotomy, and the patients in group B were processed with microfracture surgery. The Baird ankle function score and visual analog scale (VAS) were employed for evaluating the surgical efficacy and the degree of pain prior to and following surgery. The pre- and postoperative surgery-related indicators, Ankle Hindfoot Scale (AOOFAS), HSS score, lower limb alignment, and range of motion of the ankle were compared between the two groups, and changes in growth factor levels prior to and following processing were observed. Results . Overall scores were better in group A than in group B (P < 0.05 ). The operation length was longer in group A, the amount of intraoperative blood loss was greater, and the length of hospitalization was less than in group B. The VAS score 48 hours after surgery was also lower (P < 0.05 ). Postoperative AOFAS scores in group A were better, and lower limb alignment was also less than in group B (P < 0.05 ). The postoperative HSS score did not differ significantly between the two groups (P > 0.05 ). The range of plantar flexion and dorsiflexion of the ankle joint was better in group A, and the levels of endothelial growth factor (VEGF), platelet-derived growth factor (PDG), and transforming growth factor β 1 (TGF- β 1) were lower than those in group B (P < 0.05 ). The occurrence of postoperative problems did not differ between the groups (P > 0.05 ). Conclusion . Mosaic allograft osteochondral transplantation combined with corrective osteotomy has a high effective rate in the treatment of OLT, which can promote the healing of articular cartilage and the recovery of ankle joint functions, improve the range of motions of the ankle, and improve the lower limb alignment.